1999
DOI: 10.1046/j.1365-2567.1999.00817.x
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal immunogenicity and adjuvant activity of the recombinant A subunit of the Escherichia coli heat‐labile enterotoxin

Abstract: SUMMARYThe Escherichia coli heat-labile enterotoxin (LT ) is an exceptionally effective mucosal immunogen and mucosal immunoadjuvant towards coadministered antigens. Although, in general, the molecular basis of these properties is poorly understood, both the toxic ADP-ribosylation activity of the LTA subunit and the cellular toxin receptor, ganglioside, G M1 -binding properties of the LTB-pentamer have been suggested to be involved. In recent studies we found that G M1 -binding is not essential for the adjuvan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 38 publications
2
39
0
2
Order By: Relevance
“…Previous studies of CT and related bacterial toxins (such as E. coli heat-labile toxin) have emphasized the fact that the adjuvant and toxic effects of the toxin resides primarily in its A subunit, the part of the molecule that has ADP ribosyltransferase activity and accounts for its ability to activate adenylate cyclase and to generate cAMP (5). This is supported by the observation that recombinant LT-A subunit or CT-A bound to protein A (an alternative binding molecule that targets the B cells) both retain potent adjuvant activity (6,7). Of interest, it appears that the A subunit can function as an adjuvant even in the absence of ribosyltransferase activity (7).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies of CT and related bacterial toxins (such as E. coli heat-labile toxin) have emphasized the fact that the adjuvant and toxic effects of the toxin resides primarily in its A subunit, the part of the molecule that has ADP ribosyltransferase activity and accounts for its ability to activate adenylate cyclase and to generate cAMP (5). This is supported by the observation that recombinant LT-A subunit or CT-A bound to protein A (an alternative binding molecule that targets the B cells) both retain potent adjuvant activity (6,7). Of interest, it appears that the A subunit can function as an adjuvant even in the absence of ribosyltransferase activity (7).…”
Section: Discussionmentioning
confidence: 98%
“…The adjuvant effect of CT-holotoxin had been attributed to CT-A (4,5) and indeed it has recently been shown that CT-A linked to protein A, a molecule that binds to Ig on the surface of B cells or that recombinant A subunit of Escherichia coli heatlabile enterotoxin (rLT-A), a toxin molecule functionally related to CT-A, also exerts powerful adjuvant effects (6,7). Whether or not adjuvant effects are also inherent in the activity of CT-B has until recently been obscured by the fact that purified CT-B preparations used in earlier studies were probably contaminated by small amounts of CT-A (8,9).…”
Section: Holera Toxin (Ct)mentioning
confidence: 99%
“…In published studies, volumes of substances intranasally instilled into mice range from 5 l (22) to 100 l (3), with little justification for the chosen volumes. Intranasal delivery is often carried out after intraperitoneal (9, 19) or inhalation (5, 14, 15) anesthesia but has also been performed with fully awake mice (1,6,17). The position of the mouse during intranasal delivery has also varied between studies, with horizontal (13) and head-down supine (12) positions having been used.…”
mentioning
confidence: 99%
“…Application to the nasal mucosal environment in mice resulted in specific translocation of exotoxin (or exotoxin subunits) and coadministered Ags to the CNS, raising concerns about undesirable neurotoxicity (18,19). To reduce toxicity, modified exotoxins are described in which the A subunit is mutated or deleted to reduce or eliminate ribosylation activity (20,21). However, these formulations may still retain toxicity due to residual ribosylation activity, or there is an undesirable loss of adjuvanticity (15,22).…”
mentioning
confidence: 99%